2021
DOI: 10.1038/s41598-021-87929-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological factors associated with synchronous distant metastasis and prognosis of stage T1 colorectal cancer patients

Abstract: It is rare and understudied for patients with stage T1 colorectal cancer to have synchronous distant metastasis. This study was to determine the clinicopathological factors associated with distant metastasis and prognosis. T1 colorectal cancer patients diagnosed between 2010 and 2015 were obtained from the SEER database. Logistic regression was applied to determine risk factors related to distant metastasis. Cox-proportional hazard models were used to identify the prognostic factors for patients with distant m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
(14 reference statements)
2
5
1
Order By: Relevance
“…(10,(20)(21)(22)(23)(24) As Saadati et al (10) and Hassan et al (23) reported, sex was a prognostic factor in colorectal cancers both in Iran and Malaysia, but in the majority of studies, sex did not have a prognostic value. (20,(25)(26)(27) We did not find a significant relationship between sex and mortality either; yet the incidence was higher in men than in women, with a male: female ratio of 1.31. This was similar to previous reports from East Azerbaijan, (8) Iran (15) and the world.…”
Section: Discussioncontrasting
confidence: 60%
“…(10,(20)(21)(22)(23)(24) As Saadati et al (10) and Hassan et al (23) reported, sex was a prognostic factor in colorectal cancers both in Iran and Malaysia, but in the majority of studies, sex did not have a prognostic value. (20,(25)(26)(27) We did not find a significant relationship between sex and mortality either; yet the incidence was higher in men than in women, with a male: female ratio of 1.31. This was similar to previous reports from East Azerbaijan, (8) Iran (15) and the world.…”
Section: Discussioncontrasting
confidence: 60%
“…They also found that synchronous LM was an independent prognostic factor for CRC patients. Analogously, Li et al [ 56 ] employed the SEER database to construct a T1 CRC all distant metastasis model by virtue of the conventional logistic regression. Howbeit, due to the limitation of the algorithm and the approach to process data, they acquired a passable model (AUC = 0.879) with ineluctable overfitting.…”
Section: Discussionmentioning
confidence: 99%
“…A similar trend was observed for metastases in the lungs; those patients with metastases in the lungs have four times the risk of death compared to those without metastases to another site. A study by Li, Wang [ 37 ] revealed that the liver is the most affected metastasis site for patients with CRC, and they exhibited the poorest survival outcome. The anatomical situation of the liver and its portal circulation serves as a vital confluence for metastasis and recurrence routes for advancing tumours such as CRC.…”
Section: Discussionmentioning
confidence: 99%